Kepemimpinan Transformasional dan Iklim Kerja terhadap Komitmen Organisasi Anggota Polda Kalimantan Tengah: Peran Mediasi Motivasi Kerja - Swetha, I Wayan Wiratmaja; Muslim, Muh Azis (Jurnal Manajemen STIE Muhammadiyah Palopo, 2025)
This study aims to analyze the influence of transformational leadership and work climate on organizational commitment, while also examining the mediating role of work motivation among members of the Central Kalimantan Regional Police (Polda Kalimantan Tengah). This research employed a quantitative approach using a survey method. A total of 160 active police personnel were randomly selected as respondents. Data were collected through questionnaires adapted from previously validated instruments. The data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) approach, utilizing SmartPLS version 3 software. The findings reveal that transformational leadership and work climate have a positive and significant effect on organizational commitment. Furthermore, work motivation partially mediates the relationship between both independent variables and organizational commitment. These results highlight that enhancing organizational commitment is not solely dependent on leadership style and work environment, but is also significantly influenced by the motivation of personnel. This study contributes new insights by integrating transformational leadership and work climate variables in the context of the Indonesian police force, a setting that has rarely been examined simultaneously. Moreover, the inclusion of work motivation as a mediating variable offers a novel perspective on the internal mechanisms influencing organizational commitment in semi-militaristic environments such as law enforcement institutions. The practical implication of this study lies in its relevance for the management of the Central Kalimantan Regional Police to formulate effective leadership strategies and improve work climate in order to enhance work motivation, which in turn fosters greater organizational commitment. Theoretically, the study enriches the literature on organizational behavior within the security sector